INTEGRASI FITUR ZISWAF DALAM DIGITAL BANKING BANK SYARIAH: PELUANG DAN TANTANGAN (STUDI KASUS PADA BANK SYARIAH INDONESIA) - Masrina, Masrina; Lestari, Dinda (Indonesian Scientific Journal of Islamic Finance, 2025)
The digital transformation in the banking sector has created new opportunities for Islamic financial institutions to optimize social finance instruments. This study investigates the integration of Ziswaf (Zakat, Infaq, Sadaqah, and Waqf) features into Bank Syariah Indonesia's digital banking platform, analyzing the implementation process, opportunities, and challenges. Using a qualitative case study approach, data were collected through semi-structured interviews with 12 key informants, document analysis, and participatory observation of the BSI Mobile application. The findings reveal that BSI's Ziswaf digital implementation has yielded significant results, with a 172% transaction growth during 2021-2023 and collection value reaching Rp 72 billion in 2023. Key success factors include API-based technology architecture, personalized services, and enhanced transparency through impact tracking features. However, digital literacy gaps, technological infrastructure limitations in rural areas, resistance to change from traditional methods, and Sharia compliance complexities pose notable challenges. The study recommends developing a sustainable innovation model through "Digital Ziswaf Innovation Lab," implementing multi-channel education strategies, strengthening ecosystem collaboration via "Indonesia Ziswaf Digital Alliance," and utilizing data analytics to enhance service effectiveness. These initiatives can transform Islamic social finance while promoting wider Islamic financial inclusion.